About the Principles for the Protection of Lake Baikal - A. Ya. Ryzhenkov (Сибирское юридическое обозрение, 2018)
In the article the Author investigates the institutional principles of environmental law - for example, the principles for the protection of Lake Baikal as one of the varieties of specially protected natural territories. The Author argues that the Federal law “On protection of Lake Baikal” should be supplemented by a separate principle, indicating that the Baikal natural territory is a protected area of international importance, which will also require amendments to the Federal law “On specially protected natural territories”.